Answers

2015-05-09T21:09:17+05:30
                             ⇒  Factorize   :   5 √ 2 y² -  7 y - 12 √2

⇒This sum could be solved through two ways ;-
 
                      
⇒ Quadratic formula
                
                      
⇒ Synthetic division
 

Before Factorizing , we need to split the middle term in order to factorize it.

⇒ 5  √  2  y² -  7 y - 12 √2  =  5 √2 y
²  − 15 y + 8 y −12 √2 { By splitting we get                                                                                        this result }

⇒  5 y [ √ 2 y − 3 ]  +  4 √2 [ √2 y − 3 ]

⇒                [ √ 2 y − 3 ) ( 5 y + 4 √ 2]

Therefore the answer is ;-  
 [ √ 2 y − 3 ) ( 5 y + 4 √ 2]
0